Effects of Gamma Ray as Oxidative Stress on Several Blood Parameters of Male Chickens - Al-Jawwady, Yasir A.; Al-Dulamey, Quasy Kh.; Najam, Laith Ahmed (Iraqi Journal of Science, 2024)
The present work aims to detect the effects of gamma ray radiation emitted from Co-60 on several blood parameters (PCV, Hb, WBCs and  RBCs) of male chickens. Also, the potential antioxidant impact of grape seeds oil exposed to cold plasma  as a protective material to lower the damage caused by gamma ray was tested for a long time and low dose rate. Healthy male chickens were used in this study which had an age range of 2 to 3 months and  a weight range of 1.5 to 2 kg. Animals were kept in plastic cages (100 x 400  x 40 cm dimensions) within  humidity and temperature preserved at limited values. Four experimental groups were included; the first was the un-exposed control. The second group was administered with a dose of grape seed extract. The third group was exposed to gamma ray radiation only. The fourth group  was administered with a dose of grape seed extract  and irradiated with  gamma  waves. Forty male chickens   were used in this work as they were parted  and administered with the selected  doses. The control group was considered as the first group that contained  10 male chicken without  being exposed to waves of  gamma rays. The next group also contained  10 male chicken irradiated with 5 Gy/lh at  interval 7 hour/day for 20 days as second group. Another group contained 10 male chicken  and  was dealt with oil of grape seed  400 mg/kg wt) with orally administered dose for 20 days as third group. The fourth group contained 10 male chicken irradiated with 5 Gy/h at interval of 7 hour/day for 20 days and dealt with orally administered dose  (400 mg/kg wt)  of grape seed oil  for the same time. Overall groups (2-4), male chicken number became 30 used for 40.60 days at 7 hours per day. The schedule of work was achieved at 5 Gy/h of radiation equivalent dose with different exposure time for (20 and 40,60 days) on male chicken and at period 7 hours daily. The grape seed extract was bought from local market in Mosul City and filters from impure, as we found significant decrease in ratio of blood factors RBCs, WBCs, Hb and PCV with increasing of exposure time. This data changes with adding antioxidant materials as (grape seed oil) were the value of blood factors ratio enhancement by increasing the time of dose of these material compared with control group. The blood factors ratio of male chickens change with exposure time, with significant decrease by increasing exposure time, however, the protective material ( grape seed oil ) reduces the change in ratio % of the some blood factors compared with control group.